Cultivating an Attitude of Social Concern in Learning Islamic Religious Education at SMPN 27 Rejang Lebong - Fiter; Deriwanto; Hendra Harmi (Journal of Social Interactions and Humanities, 2023)
Growing social awareness is an effort to produce the next generation who have noble character and are able to position themselves in various situations. Cultivating an attitude of social concern in learning Islamic Religious Education is very important in forming character and positive moral values ​​in students to foster an attitude of social concern in learning Islamic Religious Education at SMPN 27 Rejang Lebong.